Наукове товариство імені Шевченка як суспільно-політичний проєкт Михайла Грушевського - Гирич, І.Б. (Вісник НАН України, 2024)
Speech at the anniversary session of the general meeting of the National Academy of Sciences of Ukraine, dedicated to the 150th anniversary of the Shevchenko Scientific Society, December 8, 2023.